Perlindungan Hukum Bagi Konsumen Terhadap Tindakan Sewenang-Wenang Developer Perumahan - Stefany Meylin Kurniasari; Nathaniel Elbert Gunawan; Calvin Manuel Hutomo; James Santoso (Universitas Ekasakti, 2024)
This research addresses the legal protection for consumers against arbitrary actions by housing developers. The background of this issue is the primary human need for adequate and safe housing. Developers, as business actors in the housing sector, have the responsibility to fulfill consumer rights, as regulated in Law Number 1 of 2011 concerning Housing and Residential Areas and Law Number 8 of 1999 concerning Consumer Protection. However, in practice, developers often take actions that hinder the construction of houses by consumers, thereby harming them. This research uses a normative juridical method, by collecting secondary data from books, laws, and other literature sources. The results of the research show that the actions of developers that obstruct house construction are a violation of consumer rights that require legal protection. This protection can take the form of administrative sanctions against developers, such as compensation costs and interest. Therefore, developers must be accountable for the rights granted by law to ensure consumers can build adequate and safe homes.